Nodo ancestral de restauración socio cultural tejido de reconciliación social y reincorporación del territorio (2021)
The project is located in the department of Guaviare. This department is recognized for its great natural and cultural wealth, but also for its great social problems and a marked abandonment of the state. As part of an appropriation of the territory and its difficulties, this project arises, which is developed according to a master plan framed in three important aspects, as follows: the social, the environmental context, and the productive management, so that by achieving the improvement of the infrastructure and the recovery of the social fabric of the department, the quality of life of its inhabitants be positively impacted. To fulfill this objective, a partial plan is developed in the municipality El Retorno, at 2.3 km from the urban area, its population is the central axis of the project objective, through an intercultural connection in accordance with the different communities that are found established in the sector, a social dynamic of recognition is built between the indigenous and peasant communities. Under the theory of the intersection of groups, beliefs, needs and aspirations around the productivity of the river and the importance of the Nukak park, an idea of self-efficiency materializes so that a better future can be built for the population. With the construction of this architectural project of an ancestral socio-cultural restoration node, an important step is taken in the emotional reconstruction of the victims and a deserved recognition in the history of the country.